Analisis Best Practice pada Program Layanan “Siapel Tegas” di Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Prakosa, Sakti Sigap; Pertiwi, Vidya Imanuari (VISA: Journal of Vision and Ideas, 2024)
Administrative services in Indonesia still face various issues such as the presence of intermediaries, slow e-KTP printing, and suboptimal data consolidation. The "Siapel Tegas" program at the Malang City Population and Civil Registration Office is a public service innovation aimed at improving the efficiency and effectiveness of population services. This study aims to analyze the success factors of implementation, the impact on public services, the level of actor participation, the role of leaders, public perception, encountered obstacles, and comparisons with other best practices. The research method used is a case study with a qualitative approach. The results show that "Siapel Tegas" can reduce long queues, increase service efficiency, and gain public appreciation. Leadership roles and partnerships with various parties are also key to the success of this program.